1994
DOI: 10.1203/00006450-199412000-00020
|View full text |Cite
|
Sign up to set email alerts
|

L-Selectin Is Down-regulated in Umbilical Cord Blood Granulocytes and Monocytes of Newborn Infants with Acute Bacterial Infection

Abstract: The leukocyte glycoprotein L-selectin mediates an early step in the recruitment of leukocytes to sites of inflammation. L-Selectin surface expression is rapidly down-regulated by inflammatory signals in vitro. In a prospective study, we found L-selectin expression on umbilical cord blood granulocytes and monocytes to be significantly decreased in newborn infants with acute bacterial infection compared with controls (p < 0.01). A significantly reduced L-selectin expression of both granulocytes and monocytes was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0
4

Year Published

1996
1996
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 23 publications
3
27
0
4
Order By: Relevance
“…Our findings of lower L-selectin on unstimulated term neonatal neutrophils are similar to those of previous studies in cord blood (4,5,15,16) and in neonates up to 48 h of age (4). Koenig et al (21) have reported that lysates of PMN from term neonatal cord blood have lower total L-selectin than adults, corroborating a cellular deficiency in the neonate.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Our findings of lower L-selectin on unstimulated term neonatal neutrophils are similar to those of previous studies in cord blood (4,5,15,16) and in neonates up to 48 h of age (4). Koenig et al (21) have reported that lysates of PMN from term neonatal cord blood have lower total L-selectin than adults, corroborating a cellular deficiency in the neonate.…”
Section: Discussionsupporting
confidence: 82%
“…Other studies have shown no differences with mode of delivery, as well (5,16,19,29). However, Weinschenk et al (32) did find a positive correlation between CD11b expression and labor length.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Οι ποιοτικές διαφορές τους, όπου φαίνεται να υστερούν συγκριτικά με τους ενήλικες, αφορούν στην αντίδρασή τους σε χημειοτακτικά ερεθίσματα, στην ικανότητα προσκόλλησης και κύλισης στο αγγειακό ενδοθήλιο, στην προβολή λαμινοποδίων αλλά και στους μηχανισμούς βακτηριακής λύσης [17,20]. Αξιοσημείωτο είναι το γεγονός, ότι η μειωμένη ή πολύ αυξημένη έκφραση μορίων προσκόλλησης στα ουδετερόφιλα, όπως LFA-1 στα πρόωρα και CR3 ή L -σελεκτίνης σε όλα τα νεογνά κατά τη διάρκεια σήψης, περιορίζει την κύλιση και την επακόλουθη διαπίδυσή τους [21,22]. Τέλος, διαπιστώθηκε πως οι ιδιότητες αποκοκκίωσης των νεογνικών ουδετερόφιλων δε διαφέρουν μεταξύ πρόωρων και τελειόμηνων νεογνών, ωστόσο το περιεχόμενό τους διαφέρει σημαντικά σε σχέση με τους ενήλικες.…”
Section: ανοσοκυτταρα της φυσικης ανοσιας του νεογνουunclassified